2013
DOI: 10.1016/j.jccase.2013.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Normal coronary myocardial infarct is innocent or guilty? A case of ventricular septal rupture secondary to normal coronary myocardial infarction

Abstract: Prognosis of cases of myocardial infarction with normal coronary arteries (MINCA) is known to be better than acute myocardial infarction cases with obstructive coronary lesions. A MINCA case causing ventricular septal rupture is rare. Herein, we present a 70-year-old female MINCA case which caused ventricular septal rupture which is a fatal complication of acute myocardial infarction. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 12 publications
(17 reference statements)
0
8
0
2
Order By: Relevance
“…After meticulous research, we found only 10 published cases of MINOCA-caused VSDs. [4][5][6][7][8][9][10][11][12][13] All of them treated surgically with an overall survival rate of 60%. We did not find a case of post-MINOCA VSD treated by percutaneous approach.…”
Section: Discussionmentioning
confidence: 99%
“…After meticulous research, we found only 10 published cases of MINOCA-caused VSDs. [4][5][6][7][8][9][10][11][12][13] All of them treated surgically with an overall survival rate of 60%. We did not find a case of post-MINOCA VSD treated by percutaneous approach.…”
Section: Discussionmentioning
confidence: 99%
“…11 To our knowledge, this is one of the very few case reports in the literature of a patient suffering an acute coronary syndrome with normal coronary arteries and subsequent VSR 24 h after catheterization and 30 h after hospital admission. [11][12][13][14][15] Possible explanations for the VSR after the acute coronary event may be either spasm or plaque erosion (more common in NSTEMI, younger age and absence of the 'traditional' cardiovascular risk factors) or paroxysmal atrial fibrillation, that led to transient epicardial thrombosis and/or occlusion or an ostial and isolated occlusion of a large septal perforator that could not be visualized during the coronary angiography procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Cortell et al[ 2 ] also state that the overall prognosis for such cohort of patients was considered good. However, some authors mention life-threatening mechanical MINCA complications including subepicardial aneurysm associated with ventricular septal perforation or ventricular septal rupture[ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%